Supplying Accra with Market Garden Vegetables: An Eco-Sanitary and Socio-Economic Assessment of the Knowledge, Attitudes and Practices of Producers, Traders and Processors - ASSINOU, Kokou Elom; KPOTCHOU, Koffi (Journal of Ecohumanism, 2024)
Like other cities in West Africa, Accra’s market garden sector faces a number of sustainability challenges. However, the sector’s sustainability projects focus less on the knowledge, attitudes and practices (KAP) of the stakeholders in this food system, and more on the other factors that can enhance its socio-economic, health and ecological sustainability. Thus, the research aims to assess the level of health, socio-economic and environmental sustainability of market garden vegetable production, trade and processing in the Accra metropolitan district, based on the knowledge, attitudes and practices of stakeholders. A quantitative multi-criteria evaluation approach was adopted, using a questionnaire survey targeting 156 respondents (50 producers, 63 traders and 43 processors) selected by purposive sampling. The data collected by Kobocollect were processed using Excel, Arcgis and Google Earth. Average scores and good KAP rates were calculated for all players taken together, and particularly in consideration of the key dimensions of sustainable development. The results reveal low rates for ecological (28.24%), health (20.15%), socio-economic (36.15%), technological and innovative (14.25%) knowledge, attitudes and practices, evaluated overall at 26.87%. These results are unfavorable to the achievement of the SDGs, and do not meet either standard 13 of the Global Reporting Initiative (GRI) 2023, or the principles of nutritional ecology. Hence the importance of an integrated, long-term eco-nutritional education program for all stakeholders.